THE INFLUENCE OF TERRORISM ON INTERNATIONAL TOURISM - Vovk, Svitlana (Journal of European Economy, 2017)
The article determines major trends in the development of tourism in the modern global economy and its significance for the economies of individual countries. The author considers major approaches to defining terrorism in terms of political risk, as well as its types, sources and effects. The author analyses interrelationship between terrorism and tourism and discusses ways to prevent and mitigate its negative effects.